2013
DOI: 10.3906/biy-1301-16
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression analysis of defense-related genes responsive to Tilletia indica infection in wheat

Abstract: Karnal bunt caused by Tilletia indica is a quarantine disease responsible for qualitative and quantitative losses in wheat. The present study aimed to determine the expression of defense-related genes involved in early stages of infection in response to T. indica by using the differential display reverse transcriptase-PCR method (DDRT-PCR) in susceptible (WL 711) and resistant (HD 29) cultivars of wheat. The DDRT-PCR banding profiles generated by the random primers in combination with oligo-dT primers of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The wheat importing countries have imposed strict quarantine measures and insist on a zero tolerance limit (Singh and Gogoi 2011). The disease poses an economic threat to the wheat industry due to a reduction in grain quality rather than yield (Tripathi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The wheat importing countries have imposed strict quarantine measures and insist on a zero tolerance limit (Singh and Gogoi 2011). The disease poses an economic threat to the wheat industry due to a reduction in grain quality rather than yield (Tripathi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research is being conducted intensively to identify groups of genes responsible for resistance to biotic factors (Meyer et al, 2011). It is believed that resistant genotypes can be identified in the early stages of breeding using molecular biology methods (Meyer et al, 2011;Tripathi et al, 2013). Expanding and deepening research in this area involves the integrated use of physiological and genetic approaches for a more thorough study of the condition of the plant organism, revealing the essence of integral processes that determine the level and orientation of key units of metabolism and the functioning of regulatory systems of plants at different levels of their organization.…”
Section: Introductionmentioning
confidence: 99%
“…The wheat importing countries have imposed strict quarantine measures and insist on a zero tolerance limit (Singh and Gogoi 2011). The disease poses an economic threat to the wheat industry due to reduction in grain quality rather than yield (Tripathi et al 2013). The T. indica fungus has a pathogenesis process which infects the host plant at boot stage (S2, Zadok's stage 49) by dikaryotization between compatible mating types.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that, host defense responsive genes, viz. puroindoline protein PINB (AT_KB2), β-1, 4-glucanase (AT_KB3), and chitinase (AT_KB7) were highly upregulated in the resistant cultivar (HD 29), whereas the down-regulation of these genes were observed in the susceptible (WL711) cultivar (Tripathi et al 2013). Till now, genes involved in virulence of T. indica have not been studied but few putative pathogenesis-related genes have been characterized in other fungi mainly Ustilago maydis which is a model pathogenic fungus for host-pathogen interaction studies.…”
Section: Introductionmentioning
confidence: 99%